2019
DOI: 10.1037/spy0000154
|View full text |Cite
|
Sign up to set email alerts
|

Stressors experienced in elite sport by physiotherapists.

Abstract: This study extends stress research by exploring the stressors experienced by physiotherapists' working in elite sport. The physiotherapists who were interviewed have prepared athletes and worked with them at international events (e.g., Olympic and Paralympic Games). Transcripts were analyzed using thematic analysis. Methodological rigor and generalizability were maximized through selfreflexivity and eliciting external reflections before seeking publication. Five themes were identified: I am not a Machine, This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…This is problematic when considering that coaches are performers in their own right (Thelwell et al, 2008), and when recognizing that support staff are often directly employed by sport organizations and are exposed to a plethora of organizational issues within their roles (cf. Kerai et al, 2019). However, a promising observation was that approximately 54% of the coaches in our retrieved sample were women.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…This is problematic when considering that coaches are performers in their own right (Thelwell et al, 2008), and when recognizing that support staff are often directly employed by sport organizations and are exposed to a plethora of organizational issues within their roles (cf. Kerai et al, 2019). However, a promising observation was that approximately 54% of the coaches in our retrieved sample were women.…”
Section: Discussionmentioning
confidence: 75%
“…cultural and academy issues) were experienced among performance staff. Similarly, Kerai et al (2019) found that high workload, working in a 'performance-and-risk' culture, interpersonal conflicts, scrutiny in decision-making, and working beyond their remit were significant organizational stressors for physiotherapists working with international athletes. explored the experiences of 40 sport science and management personnel, finding that stressors related to interpersonal issues (e.g.…”
Section: Organizational Stressorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wellbeing and mental health of coaches is an under researched area (Norris et al, 2017), though even less is known about the level of, and factors affecting, the wellbeing and mental health of sport science practitioners working within elite sport. It has been identified that physiotherapists working within the high-performance setting must cope effectively with a high workload, power-relationships, and the moral/ethical conflict they often experience within their role (Kerai et al, 2019). Similarly, sport psychologists appear to encounter multiple stressors that include factors intrinsic to sport psychology, interpersonal demands, organizational roles, career/development issues, and organizational climate of the profession (Cropley et al, 2016).…”
mentioning
confidence: 99%
“…11 Additionally, an excessive workload, post-competition loss, and a feeling of isolation have been identified as risk factors to elite coach and support staff wellbeing, while effective organizational culture, transformational leadership, and access to quality social support were identified as protective factors. 1 For example, in a qualitative study exploring stressors experienced by physiotherapists working in elite sport, Kerai et al 12 found that sports physiotherapists experience various stressors including workload, power relationships and ethical conflicts leading to outcomes such as work-life conflicts and job insecurity.…”
mentioning
confidence: 99%